Diagnosis and therapy using double-balloon endoscopy for small bowel disease: experience from a Chinese tertiary hospital - Anning Yin; Wei Hu; Liang Zhao; Yijuan Ding; Honggang Yu (Journal of International Medical Research)
Objective To evaluate the clinical efficacy of double-balloon endoscopy (DBE) for small bowel disease (SBD). Methods The clinical and endoscopic data of patients who underwent DBE in a Chinese tertiary hospital from January 2006 to December 2019 were retrospectively reviewed. The patients were divided into three groups by age: the young group (<45 years), middle-aged group (45–65 years), and older group (>65 years). Results In total, 1177 patients who underwent 2134 DBE procedures were included. The anterograde and retrograde route was used in 1111 and 1023 procedures, respectively. The most common reason for performing DBE was suspected small bowel bleeding (SSBB) (53.1%), and the most common SBD was Crohn's disease (CD) (18.1%). Hemostasis was the predominant endoscopic therapy (54.3%). The total complication rate was 0.8%. The incidence of CD was highest in the young group, and the incidence of tumors was highest in the older group; these findings were consistent both among the overall patient population and among patients with SSBB. Conclusions DBE is effective and safe for the diagnosis and treatment of SBD and is considered to have great potential as a first-line method for diagnosing SBD.